Rh(III) Catalyzed Oxidation of Cyclic Alcohols by Sodium Periodate in Acidic Medium - Srivastava, Sheila; Srivastava, Sangeeta; Singh, Shalini (Asian Journal of Chemistry, 2010)
Kinetics investigation on Rh(III) catalyzed oxidation of cyclopentanol and cyclohexanol by acidic solution of sodium periodate (NaIO4) in the presence of mercury(II) acetate as a scavenger has been carried out in the temperature range of 30-45 ºC.The reaction exhibits first order kinetics with respect to substrate and catalyst whereas zero order with respect to oxidant i.e. NaIO4.The rate shows no effect with increasing concentration of [H+]. The influence of [Hg(OAc)2], ionic strength and [Cl–] on the rate was found to be insignificant. The effect of varing percentage of AcOH on reaction rate was also examined. Various activation parameters have been calculated from rate measurements and the rate law derived on the basis of obtained data.